Changing epidemiology of human parvovirus 4 infection in sub-Saharan Africa. - Sharp, C; Vermeulen, M; Nébié, Y; Djoko, C; LeBreton, M; Tamoufe, U; Rimoin, A; Kayembe, P; Carr, J; Servant-Delmas, A; Laperche, S; Harrison, G; et al. (2010)
Human parvovirus 4 infections are primarily associated with parenteral exposure in western countries. By ELISA, we demonstrate frequent seropositivity for antibody to parvovirus 4 viral protein 2 among adult populations throughout sub-Saharan Africa (Burkina Faso, 37%; Cameroon, 25%; Democratic Republic of the Congo, 35%; South Africa, 20%), which implies existence of alternative transmission routes.